Current Research Studies of Mg–Ca–Zn Biodegradable Alloys Used as Orthopedic Implants—Review - Bogdan Istrate; Corneliu Munteanu; Iulian-Vasile Antoniac; Ștefan-Constantin Lupescu (Crystals, 2022)
Biodegradable alloys and especially magnesium-based alloys are considered by many researchers as materials to be used in medicine due to their biocompatibility and excellent mechanical properties. Biodegradable magnesium-based materials have applications in the medical field and in particular in obtaining implants for small bones of the feet and hands, ankles, or small joints. Studies have shown that Mg, Zn, and Ca are found in significant amounts in the human body and contribute effectively and efficiently to the healing process of bone tissue. Due to its biodegradability, magnesium alloys, including Mg–Ca–Zn alloys used in the manufacture of implants, do not require a second surgery, thus minimizing the trauma caused to the patient. Other studies have performed Mg–Ca–Zn system alloys with zinc variation between 0 and 8 wt.% and calcium variation up to 5 wt.%, showing high biocompatibility, adequate mechanical properties, and Mg2Ca and Mg6Ca2Zn compounds in microstructure. Biocompatibility is an essential factor in the use of these materials, so that some investigations have shown a cell viability with values between 95% and 99% compared with the control in the case of Mg–0.2Ca–3Zn alloy. In vivo analyses also showed no adverse reactions, with minimal H<semantics>2</semantics> release. The aim of this review includes aspects regarding microstructure analysis and the degradation mechanisms in a specific environment and highlights the biocompatibility between the rate of bone healing and alloy degradation due to rapid corrosion of the alloys.